Gain-scheduled PI tracking control on stochastic nonlinear systems with partially known transition probabilities - Yin, YanYan; Shi, P.; Liu, F. (Elsevier, 2011)
This paper studies the problem of continuous gain-scheduled PI tracking control on a class of stochastic nonlinear systems subject to partially known jump probabilities and time-varying delays. First, gradient linearization procedure is used to construct model-based linear stochastic systems in the vicinity of selected operating states. Next, based on stochastic Lyapunov stabilization analysis, sufficient conditions for the existence of a PI tracking control are established for each linear model in terms of linear matrix inequalities. Finally, continuous gain-scheduled approach is employed to design continuous nonlinear PI tracking controllers on the entire nonlinear jump system. Simulation example is given to illustrate the effectiveness of the developed design techniques. © 2011 The Franklin Institute © 2011 Published by Elsevier Ltd. on behalf of The Franklin Institute.